MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY IN RETELLING NARRATIVE STORY - Putri Nurhalizah; I Made Sujana; Lalu Ali Wardana (Program Studi Pendidikan Bahasa Inggris, 2021)
The purpose of this study is to find out whether or not the mind mapping technique is effective to improve students' speaking ability in retelling narrative stories. It is experimental research using pretest and posttest design. The population of this study was 8th-grade students of Junior High School 8 Mataram, consisting of 160 students. Of the population, 20 students were selected using a purposive sampling technique as control group and other 20 students as experimental group. The data of pretest and posttest were collected using speaking tests, assessed by two assessors to ensure the reliability of the assessment. The collected data were then analyzed quantitatively. From the analysis it was found that the degree of freedom was 38, t – table was 1.68 at significance level 0.05 (95%) and 3.31 at significance level 0.01 (99%), while the value of t-test (t0) was 9.875, higher than t – table distribution value which means that the null hypothesis (H0) is rejected. Thus, it is concluded that the Mind Mapping technique is effective in improving students' speaking ability in retelling the narrative story at 8th grade Junior High School 8 Mataram.